Acrylic-based ceramic composite nanofiber solid electrolyte and preparation method thereof
By using electrospinning technology to form a three-dimensional ceramic frame in acrylic-based ceramic composite nanofiber solid electrolytes, the mechanical fragility and interface resistance problems of inorganic ceramic solid electrolytes in flexible energy storage devices are solved, and high energy density and cyclic stability are achieved flexible battery material.
Patent Information
- Application Number
- CN202210246386.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-03-14
AI Technical Summary
The existing inorganic ceramic solid electrolytes have mechanical fragility and high interface resistance problems in flexible energy storage devices, limiting their application in wearable electronic products.
The solid electrolyte of acrylic-based ceramic composite nanofiber is used to uniformly disperse oxide ceramic nanoparticles in the acrylic solution through electrospinning technology to form a three-dimensional ceramic nanofiber frame, providing a continuous ion transmission path and improving mechanical flexibility.
The good electrochemical performance and mechanical flexibility of acrylic-based ceramic composite nanofiber solid electrolyte is achieved, and the energy density and cycle stability of lithium batteries are improved, and the needs of flexible batteries are met.
Smart Images

Figure CN114695949B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an energy storage functional material, in particular to an acrylic fiber-based ceramic composite nanofiber solid electrolyte and a preparation method thereof, belonging to the technical field of energy storage materials. Background Art
[0002] With the increasing demand for wearable smart electronic products and smart textiles, there is a need for corresponding flexible energy storage devices to match them; lithium batteries have become one of the most promising flexible energy storage devices due to their high energy density, power density, and environmental friendliness. However, current commercial lithium-ion batteries have the defects of insufficient energy density and low safety due to the use of organic flammable liquid electrolytes, which limits their use as flexible energy storage devices and cannot match wearable electronic products.
[0003] To solve the inherent defects of commercial liquid lithium-ion batteries, solid electrolytes can be used instead of liquid electrolytes. Compared with liquid electrolytes, solid electrolytes are non-flammable and have no leakage risk, which can effectively solve the safety hazards of batteries. In addition, solid electrolytes have a wide electrochemical window, which can be used with lithium metal negative electrodes and high-voltage positive electrode materials to greatly improve the energy density of batteries. Inorganic ceramic solid electrolytes in solid electrolytes have high ionic conductivity (10 at room temperature). -4 S cm -1 ), wide electrochemical window, and chemical stability with lithium metal, and are favored by researchers at home and abroad. However, inorganic ceramic solid electrolytes are rigid and fragile, and there is a high interface resistance between them and the electrodes, which cannot meet the needs of flexible energy storage devices for flexibility and wearability.
[0004] An effective solution to the problems of inorganic ceramic solid electrolytes is to combine inorganic ceramic nanoparticles with high ionic conductivity with a flexible polymer matrix, that is, to use oxide ceramic nanoparticles as active fillers and disperse them in a polymer matrix to construct a composite system, so as to give full play to the complementary advantages of the two. Composite solid electrolytes have both the high ionic conductivity of inorganic ceramic solid electrolytes and the excellent mechanical flexibility of polymers, and are ideal candidates for solid electrolytes. However, during the preparation of composite solid electrolytes, due to the huge difference in surface energy between inorganic ceramics and organic polymers, ceramic nanofillers are prone to agglomeration, which seriously affects the overall ion transport of the composite solid electrolyte. In addition, since the ceramic nanofillers are dispersed from each other, a continuous ion transport path cannot be formed, which reduces the overall ion conductivity of the composite solid electrolyte.
[0005] In order to optimize the structure of composite solid electrolytes and improve the uniformity of ceramic nanofiller dispersion, it is an ideal choice to design a 3D interconnected ceramic nanofiber framework to replace the dispersed ceramic nanoparticles. Ceramic nanofibers have a long-distance continuous ion transport path in a mesh, which can not only achieve rapid migration of lithium ions, improve the rate performance of solid-state batteries, and achieve rapid charging and discharging; but also avoid the separation between inorganic ceramics and organic polymers, further improving the mechanical flexibility of composite solid electrolytes and the overall energy density of batteries. Summary of the invention
[0006] The present invention provides an acrylic-based ceramic composite nanofiber solid electrolyte having good mechanical flexibility. When used as an electrolyte material for a solid-state lithium battery, it has good electrochemical properties and can meet the requirements of a flexible battery. It can be used as an electrolyte material for a solid-state lithium battery.
[0007] The present invention also provides a method for preparing the acrylic-based ceramic composite nanofiber solid electrolyte.
[0008] The technical solution adopted by the present invention to solve the technical problem is:
[0009] A method for preparing an acrylic-based ceramic composite nanofiber solid electrolyte, the method comprising the following steps:
[0010] S1. Preparation of electrospinning precursor solution:
[0011] a. dissolving acrylic yarn and conductive lithium salt in a solvent N,N-dimethylformamide to obtain an acrylic solution;
[0012] b. Adding oxide-type ceramic nanoparticles and zinc acetate (Zn(Ac)2) to the acrylic fiber solution, stirring and dispersing them uniformly at room temperature, and then stirring at a temperature of 70-90° C. to obtain an electrospinning precursor solution;
[0013] The amount of oxide-type ceramic nanoparticles added is 5-20% of the weight of the acrylic yarn, and the amount of zinc acetate added is 15-30% of the weight of the acrylic yarn;
[0014] S2. Preparation of acrylic-based oxide-type ceramic nanofibers: The electrospinning precursor solution obtained in S1 is electrospinned into a nanofiber membrane, and then vacuum dried at 60±10° C. to obtain acrylic-based oxide-type ceramic nanofibers;
[0015] S3. Preparation of organic polymer solid electrolyte solution:
[0016] The polymer that can be used as a solid electrolyte and the conductive lithium salt are vacuum dried in a temperature range below their respective melting points for later use;
[0017] Then, the polymer and the conductive lithium salt are dissolved in the organic solvent acetonitrile and stirred sufficiently to form a uniformly mixed organic polymer solid electrolyte solution; the weight ratio of the polymer to the conductive lithium salt is 2 to 4:1;
[0018] S4. Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0019] Finally, the acrylic-based oxide-type ceramic nanofiber obtained in S2 is placed on a mold (usually made of polytetrafluoroethylene), and a layer of organic polymer solid electrolyte solution obtained in S3 is poured on the surface;
[0020] After the organic solvent acetonitrile is completely volatilized, the mold is removed and vacuum dried to obtain an acrylic fiber-based ceramic composite nanofiber solid electrolyte.
[0021] In view of the problems existing in the current composite solid electrolytes, the present invention proposes a method for preparing an acrylic-based ceramic composite nanofiber solid electrolyte, that is, dispersing ceramic fillers in an acrylic solution, and preparing a three-dimensional mesh oxide ceramic framework by an electrospinning method, which is used as a filler for a flexible composite solid electrolyte. By optimizing the dispersion of oxide ceramic fillers in acrylic fibers and constructing a three-dimensional ceramic nanofiber ion-conducting framework in a polymer matrix, it is possible to maintain uniform dispersion of ceramic fillers to a certain extent and to provide Li + Provides a continuous and fast three-dimensional ion transport channel.
[0022] The present invention is simple to prepare and can be mass-produced. The obtained acrylic fiber-based ceramic composite nanofiber solid electrolyte can form a three-dimensional ion-conducting path, which can not only avoid the mutual agglomeration of ceramic fillers, but also can provide Li + The transmission provides a fast and continuous path. The resulting acrylic fiber-based ceramic composite nanofiber solid electrolyte has good mechanical flexibility, and the all-solid-state lithium battery based on acrylic fiber-based ceramic composite nanofiber solid electrolyte also exhibits high reversible capacity and long-term cycle stability, which can meet the needs of flexible batteries.
[0023] Preferably, the acrylic yarn is textile waste material (such as waste fiber, waste yarn, and broken textile fabrics) for civil use and clothing, or leftover acrylic yarn.
[0024] Preferably, the weight ratio of the acrylic yarn to the conductive lithium salt in step a of S1 is 1:0.8-1.
[0025] Preferably, the preparation method of the oxide-type ceramic nanoparticles described in S1 is: placing a metal ion precursor salt containing an oxide-type ceramic solid electrolyte in a ball mill, adding an excess of Li2CO3 precursor salt as a compensator, mixing the precursor salt powder in propylene glycol, ball milling, calcining, and ball milling again to obtain oxide-type ceramic nanoparticles;
[0026] The metal ion precursor salt is selected from garnet type, NASICON type, perovskite type or antiperovskite type ceramic precursor salt.
[0027] Preferably, the stirring temperature of the electrospinning precursor solution in S1 is 70-80°C.
[0028] Preferably, in step b of S1, the amount of zinc acetate added is 20-30% of the weight of the acrylic yarn, and the best amount of zinc acetate added is 25%.
[0029] Preferably, in S2, the spinning parameters are static voltage 10-15 kV, spinning distance 10-15 cm, spinning solution flow rate 0.5-1.0 mL / h, and spinning drum speed 300-400 rpm.
[0030] Preferably, in S1, the conductive lithium salt is selected from one or more of lithium halide (LiX, X = F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4);
[0031] In S3, the polymer is selected from a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC); the conductive lithium salt is selected from one or more of lithium halides (LiX, X=F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
[0032] Preferably, the polymer and the conductive lithium salt in S3 are stirred in acetonitrile for 24-48 hours.
[0033] Preferably, the vacuum drying temperature of the acrylic-based ceramic composite nanofiber solid electrolyte in S4 is 50° C.±5° C., and the drying time is 24 h±5 h.
[0034] Preferably, the stirring temperature of the electrospinning precursor solution in S1 is 70-80°C.
[0035] A acrylic fiber-based three-dimensional ceramic nanofiber composite solid electrolyte for a flexible solid-state lithium battery. The composite material is prepared by the preparation method.
[0036] The present invention uses civilian acrylic yarn as raw material and textile waste to prepare a composite solid electrolyte to achieve innovation in the energy storage system and high-quality utilization of textile waste, and demonstrates its great application potential in the preparation of low-cost, high-performance lithium metal solid-state batteries.
[0037] The present invention first prepares ceramic nanoparticles; then the ceramic particles are evenly dispersed in an acrylic solution, and an acrylic-based oxide-type ceramic nanofiber membrane is prepared by electrospinning technology; finally, the acrylic-based oxide-type ceramic composite nanofiber is compounded with a "polymer-conductive lithium salt" system by casting to obtain an acrylic-based ceramic composite nanofiber solid electrolyte, which can be applied to the energy storage field represented by flexible all-solid-state lithium batteries. The method of the present invention has the following characteristics:
[0038] (1) The present invention is simple to prepare, the reaction conditions are easy to control and implement, and can be produced on a large scale;
[0039] (2) Compared with traditional nano-ceramic particle fillers, acrylic-based ceramic nanofiber frameworks have a 3D interconnected ion transport network that can accelerate Li + Migration in solid electrolytes;
[0040] (3) The three-dimensional structure of the acrylic-based oxide-type ceramic nanofiber framework and its large specific surface area can promote the "polymer-conductive lithium salt" system to penetrate into the ceramic framework, forming a continuous and tight inorganic ceramic / organic polymer interface, thereby improving the Li + The transfer rate at the interface;
[0041] (4) The obtained acrylic-based ceramic nanofiber composite solid electrolyte can be applied to flexible all-solid-state lithium batteries, and has good electrochemical properties, mechanical flexibility and high safety;
[0042] (5) The preparation method of ceramic nanofibers electrospun from acrylic yarn can be extended to other waste textile materials, such as waste fibers, waste yarns, and shredded textiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1The scanning electron microscope (SEM) images of acrylic / Zn(Ac)2 nanofibers with different Zn(Ac)2 contents (Zn(Ac)2 dosages were 0, 20%, 30%, 40%, and 60%) prepared to explore the effect of Zn(Ac)2 dosage on subsequent acrylic spinning, and the EIS graph of a stainless steel / solid electrolyte / stainless steel symmetric cell with 0 amount of ceramic nanoparticles added to the acrylic-based composite nanofiber solid electrolyte;
[0044] Among them, (a) to (e) are scanning electron microscope (SEM) photos of Zn(Ac)2 dosage of 0, 20%, 30%, 40%, and 60% respectively;
[0045] Figure 2 is a scanning electron microscope (SEM) photograph of the LLZTO oxide ceramic nanoparticles prepared in Example 1;
[0046] Figure 3 is a SEM photograph of the acrylic-based oxide-type LLZTO ceramic nanofiber prepared in Example 1;
[0047] Figure 4 is a surface SEM photograph of the acrylic fiber-based LALZO ceramic composite nanofiber solid electrolyte prepared in Example 2;
[0048] Figure 5 is an electrochemical impedance spectrum (EIS) graph of a stainless steel / solid electrolyte / stainless steel symmetric cell of acrylic fiber-based LALZO ceramic composite nanofiber solid electrolyte with different LALZO contents prepared in Example 3;
[0049] Among them, (a) to (e) are electrochemical impedance spectroscopy (EIS) graphs of stainless steel / solid electrolyte / stainless steel symmetric cells with LALZO dosage of 0, 5%, 10%, 15%, and 20%, respectively;
[0050] Figure 6 is an Arrhenius curve of a stainless steel / solid electrolyte / stainless steel symmetric battery of an acrylic fiber-based LALZO ceramic composite nanofiber solid electrolyte prepared in Example 3;
[0051] Figure 7 It is a line sweep voltammetry (LSV) diagram of a Li / solid electrolyte / stainless steel battery with no ceramic nanoparticles added and 15% of the acrylic fiber-based LLZTO ceramic composite nanofiber solid electrolyte prepared in Example 4;
[0052] Figure 8 1 is a cycle performance diagram of a Li / solid electrolyte / Li symmetric battery of an acrylic fiber-based LLZTO ceramic composite nanofiber solid electrolyte prepared in Example 4;
[0053] Fig. 9 This is the long-term cycle performance of the Li / solid electrolyte / LiFePO4 all-solid-state battery with the acrylic-based LLTO ceramic composite nanofiber solid electrolyte prepared in Example 5. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0055] In the present invention, unless otherwise specified, all parts and percentages are by weight, and all equipment and raw materials can be purchased from the market or are commonly used in the industry.
[0056] In the following embodiments, the acrylic yarn used is acrylic yarn for civil use, clothing use, textile waste materials (such as waste fibers, waste yarns, and broken textiles) or leftovers.
[0057] Experimental study on the effect of zinc acetate dosage on target electrospinning precursor solution
[0058] Test conditions:
[0059] Preparation of acrylic yarn / zinc acetate electrospinning precursor solution:
[0060] 1g of civilian acrylic yarn and different contents of Zn(Ac)2 were dissolved in 9g of N,N-dimethylformamide solvent, stirred at room temperature to obtain an acrylic / Zn(Ac)2 composite solution, and then stirred at a temperature of 70-90°C to obtain an acrylic / Zn(Ac)2 electrostatic spinning precursor solution, wherein the Zn(Ac)2 powder was 0%, 20%, 30%, 40%, and 60% of the acrylic yarn content; under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, the precursor solution was spun into a nanofiber membrane, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain an acrylic / Zn(Ac)2 composite nanofiber.
[0061] The viscosity and conductivity of the acrylic / Zn(Ac)2 electrospinning precursor solution with Zn(Ac)2 added at 0%, 20%, 30%, 40%, and 60% of the weight of the acrylic yarn were investigated; the diameter of the acrylic / Zn(Ac)2 composite nanofibers prepared with different Zn(Ac)2 contents were investigated. The experimental results are shown in Figure 1 shown.
[0062] According to the above test results and Figure 1It can be seen that the present invention additionally adds a small amount of zinc acetate (Zn(Ac)2) to the electrospinning precursor solution to achieve electrospinning of the electrospinning precursor solution. The inventor has verified through multiple experiments that the acrylic fiber / Zn(Ac)2 composite nanofibers prepared by electrospinning without adding zinc acetate have poor conductivity and uneven diameter distribution; after adding Zn(Ac)2, the conductivity of the acrylic spinning solution increases, the electrostatic repulsion acting on the solution increases, the surface tension of the jet decreases, the diameter of the obtained fiber decreases, and the fiber diameter size distribution is uniform; with the increase of Zn(Ac)2 content, although the electrostatic repulsion increases, the increase of salt content will increase the viscosity of electrospinning, and the increase in viscosity will increase the surface tension of the jet, which will increase the stability of the jet, so that the diameter of the fiber is still increased, and the situation of fiber diameter concurrence occurs (when the Zn(Ac)2 dosage is 40% and 60%). Therefore, according to various factors and the actual requirements of this experiment, in order to obtain the appropriate composite spinning precursor viscosity and diameter of the subsequent acrylic-based ceramic composite nanofiber, as a preferred embodiment, the experiment described in the present invention is based on the addition of zinc acetate to 20-30% of the weight of the acrylic yarn for subsequent experimental premise, in preparation for the subsequent preparation of the target product described in the present invention. And the addition of Zn(Ac)2 to the acrylic yarn spinning solution can not only increase the viscosity of the spinning solution and increase the stability of the jet, but also reduce the crystallinity of the acrylic polymer, contributing to the subsequent research of composite solid electrolytes.
[0063] The addition of Zn(Ac)2 to the electrospinning precursor solution of acrylic-based ceramic composite nanofibers with acrylic yarn as the substrate is an unexpected discovery of the inventors, which was obtained through experiments in more tests.
[0064] Example 1
[0065] A method for preparing an acrylic fiber-based ceramic composite nanofiber solid electrolyte, the specific steps of the method are as follows:
[0066] (1) Preparation of oxide-type ceramic nanoparticles:
[0067] 3.375mmol Li2CO3, 1.5mmol La2O3, 1.75mmol ZrO2, and 0.125mmol Ta2O5 precursor salts were placed in a ball mill. Considering the volatilization of lithium and the Li 6.75 La3Zr2T 0.25 O 12To decompose (LLZTO), an additional 15% Li2CO3 needs to be added. The mixed ball milling was carried out for 12 hours using isopropanol as the ball milling medium, using zirconium oxide grinding balls, and the ball milling speed was 300rpm. The ball-milled mixture was dried in an oven at 80°C for 12 hours. Then, it was calcined at 900°C for 12 hours, pressed into shape at a pressure of 15MPa, sintered in an air atmosphere, and then ball milled for 12 hours to obtain cubic oxide ceramic nanoparticles. The scanning electron microscope (SEM) photo of LLZTO cubic oxide ceramic nanoparticles is shown in Figure 1 .
[0068] (2) Preparation of acrylic-based oxide-type ceramic nanofibers:
[0069] 1g of civilian acrylic yarn and 0.08g of conductive lithium salt were dissolved in 9g of N,N-dimethylformamide solvent, and stirred at room temperature to obtain an acrylic solution; 0.15g of ceramic nanoparticles and 0.25g of zinc acetate (Zn(Ac)2) were added to the acrylic solution, and stirred and dispersed evenly at room temperature to obtain an acrylic-based ceramic composite solution, which was stirred at 80°C for 90min to obtain an electrospinning precursor solution; the precursor solution was spun into a nanofiber membrane under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain acrylic-based oxide-type LLZTO ceramic nanofibers. Scanning electron microscope (SEM) photos of acrylic-based ceramic composite nanofibers are shown in Figure 2 .
[0070] (3) Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0071] Ⅰ. 2.45 g PEO and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile and stirred thoroughly to form a uniformly mixed organic polymer solid electrolyte solution;
[0072] II. Placing the acrylic-based oxide-type LLZTO ceramic nanofiber obtained in step (2) on a polytetrafluoroethylene mold, and pouring a layer of the PEO-LiTFSI organic polymer solid electrolyte solution obtained in step I on the surface thereof;
[0073] III. After the organic solvent acetonitrile is completely volatilized, the composite solid electrolyte membrane is separated from the mold and vacuum dried at 50°C for 24 hours to remove residual acetonitrile and adsorbed H2O, and the total thickness of the acrylic fiber-based LLZTO ceramic composite solid electrolyte is controlled at 90-110 μm.
[0074] The scanning electron microscope (SEM) photograph of the LLZTO oxide ceramic nanoparticles prepared in Example 1 is as follows: Figure 2 As shown, the ceramic nanoparticles present a cubic phase structure, with uniform particle morphology, dense morphology and well-grown particles.
[0075] The SEM photo of the acrylic oxide-type LLZTO ceramic nanofiber prepared in Example 1 is as follows: Figure 3 As shown in the figure, the ceramic nanoparticles are evenly dispersed on the nanofibers and the fiber structure remains intact. This not only avoids the aggregation of ceramic fillers in the composite solid electrolyte, but also provides a good solution for Li + It provides a continuous and fast transmission path, which helps to improve the ionic conductivity of the electrolyte. In addition, there are many pores in the acrylic oxide-based LALZO ceramic nanofiber framework, which is conducive to the subsequent "polymer-conductive lithium salt" solution to fully penetrate into the porous ceramic network, forming a tight ceramic / polymer interface, thereby increasing the ion conduction rate at the interface and reducing the interface resistance of the two.
[0076] The surface SEM photo of the acrylic fiber-based LALZO ceramic composite nanofiber solid electrolyte prepared in Example 1 is as follows: Figure 4 As shown, the surface of the ceramic composite nanofiber solid electrolyte is flat and smooth with a few textures. This is due to the penetration of the organic polymer solution into the ceramic nanofibers during the pouring of the PEO-LiTFSI polymer solid electrolyte solution and the volatilization of acetonitrile in the solution after subsequent pouring.
[0077] Example 2
[0078] A method for preparing an acrylic fiber-based ceramic composite nanofiber solid electrolyte, the specific steps of the method are as follows:
[0079] (1) Preparation of oxide-type ceramic nanoparticles:
[0080] 3.14mmol Li2CO3, 1.5mmol La2O3, 2mmol ZrO2, and 0.12mmol Al2O3 precursor salt were placed in a ball mill. Considering the volatilization of lithium and the Li 6.28 Al 0.24 La3Zr2O 12 To decompose LALZO, 15% Li2CO3 needs to be added. The mixed material is ball-milled for 12 hours with isopropanol as the ball-milling medium, and the zirconia grinding ball is used at a ball-milling speed of 300 rpm. The ball-milled mixture is dried in an oven at 80°C for 12 hours. Then, it is calcined at 900°C for 12 hours, pressed under a pressure of 15 MPa, sintered in an air atmosphere, and then ball-milled for 12 hours to obtain oxide-type LALZO ceramic nanoparticles.
[0081] (2) Preparation of acrylic-based oxide-type ceramic nanofibers:
[0082] 1g of civilian acrylic yarn and 0.08g of conductive lithium salt were dissolved in 9g of N,N-dimethylformamide solvent, and stirred at room temperature to obtain an acrylic solution; 0.15g of ceramic nanoparticles and 0.25g of zinc acetate (Zn(Ac)2) were added to the acrylic solution, stirred and dispersed evenly at room temperature to obtain an acrylic-based ceramic composite solution, which was stirred at 80°C for 90min to obtain an electrospinning precursor solution; under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, the precursor solution was spun into a nanofiber membrane, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain acrylic-based oxide-type LALZO ceramic nanofibers.
[0083] (3) Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0084] Ⅰ. 2.45 g PEO and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile and stirred thoroughly to form a uniformly mixed organic polymer solid electrolyte solution;
[0085] II. Placing the acrylic-based oxide-type ceramic nanofibers obtained in step (2) on a polytetrafluoroethylene mold, and pouring a layer of the PEO-LiTFSI organic polymer solid electrolyte solution obtained in step I on the surface thereof;
[0086] III. After the organic solvent acetonitrile is completely volatilized, the composite solid electrolyte membrane is separated from the mold and vacuum dried at 50°C for 24 hours to remove the residual acetonitrile and adsorbed H2O to obtain an acrylic fiber-based LALZO ceramic composite solid electrolyte. The total thickness of the acrylic fiber-based ceramic composite nanofiber solid electrolyte is controlled at 90-110 μm.
[0087] Example 3
[0088] A method for preparing an acrylic fiber-based ceramic composite nanofiber solid electrolyte, the specific steps of the method are as follows:
[0089] (1) Preparation of oxide-type ceramic nanoparticles:
[0090] 3.14mmol Li2CO3, 1.5mmol La2O3, 2mmol ZrO2, and 0.12mmol Al2O3 precursor salt were placed in a ball mill. Considering the volatilization of lithium and the Li 6.28 Al 0.24La3Zr2O 12 To decompose LALZO, 15% Li2CO3 needs to be added. The mixed material is ball-milled for 12 hours with isopropanol as the ball-milling medium, and the zirconia grinding ball is used at a ball-milling speed of 300 rpm. The ball-milled mixture is dried in an oven at 80°C for 12 hours. Then, it is calcined at 900°C for 12 hours, pressed under a pressure of 15 MPa, sintered in an air atmosphere, and then ball-milled for 12 hours to obtain oxide-type LALZO ceramic nanoparticles.
[0091] (2) Preparation of acrylic-based oxide-type ceramic nanofibers:
[0092] 1g of civilian acrylic yarn and 0.08g of conductive lithium salt are dissolved in 9g of N,N-dimethylformamide solvent, and stirred at room temperature to obtain an acrylic solution; the oxide-type ceramic nanoparticles prepared in step (1) and 0.25g of zinc acetate (Zn(Ac)2) are added to the acrylic solution, and stirred and dispersed uniformly at room temperature to obtain an acrylic-based ceramic composite solution, and stirred at 80°C for 90min to obtain an electrostatic spinning precursor solution, wherein the oxide-type LALZO ceramic nanoparticles are 0%, 5%, 10%, 15%, and 20% of the content of the acrylic yarn; the precursor solution is spun into a nanofiber membrane under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain acrylic-based oxide-type LALZO ceramic nanofibers.
[0093] (3) Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0094] Ⅰ. 2.45 g PVDF and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile and stirred thoroughly to form a uniformly mixed organic polymer solid electrolyte solution;
[0095] II. Placing the acrylic-based oxide-type ceramic nanofibers obtained in step (2) on a polytetrafluoroethylene mold, and pouring a layer of the PVDF-LiTFSI organic polymer solid electrolyte solution obtained in step I on the surface thereof;
[0096] III. After the organic solvent acetonitrile is completely evaporated, the composite solid electrolyte membrane is separated from the mold and vacuum dried at 50°C for 24 hours to remove residual acetonitrile and adsorbed H2O, thereby obtaining an acrylic fiber-based LALZO ceramic composite solid electrolyte with a total thickness controlled at 90-110 μm.
[0097] The electrochemical impedance spectra (EIS) of the stainless steel / solid electrolyte / stainless steel symmetric cells of the acrylic fiber-based LALZO ceramic nanofiber composite solid electrolyte with different LALZO contents prepared in this example are shown in FIG. Figure 5 ; Arrhenius curve see Figure 6 .
[0098] Example 4
[0099] A method for preparing an acrylic fiber-based ceramic composite nanofiber solid electrolyte, the specific steps of the method are as follows:
[0100] (1) Preparation of oxide-type ceramic nanoparticles:
[0101] 3.375mmol Li2CO3, 1.5mmol La2O3, 1.75mmol ZrO2, and 0.125mmol Ta2O5 precursor salts were placed in a ball mill. Considering the volatilization of lithium and the Li 6.75 La3Zr2T 0.25 O 12 To decompose (LLZTO), 15% Li2CO3 needs to be added. The mixed ball milling is carried out for 12 hours with isopropanol as the ball milling medium, and the zirconia grinding ball is used at a ball milling speed of 300rpm. The ball-milled mixture is dried in an oven at 80°C for 12 hours. Then, it is calcined at 900°C for 12 hours, pressed under a pressure of 15MPa, sintered in an air atmosphere, and then ball milled for 12 hours to obtain oxide-type LLZTO ceramic nanoparticles.
[0102] (2) Preparation of acrylic-based oxide-type ceramic nanofibers:
[0103] 1g of civilian acrylic yarn and 0.08g of conductive lithium salt were dissolved in 9g of N,N-dimethylformamide solvent, and stirred at room temperature to obtain an acrylic solution; 0.15g of ceramic nanoparticles and 0.25g of zinc acetate (Zn(Ac)2) were added to the acrylic solution, stirred and dispersed evenly at room temperature to obtain an acrylic-based ceramic composite solution, which was stirred at 80°C for 90min to obtain an electrospinning precursor solution; under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, the precursor solution was spun into a nanofiber membrane, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain acrylic-based oxide-type LLZTO ceramic nanofibers.
[0104] (3) Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0105] Ⅰ. 2.45 g PVDF and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile and stirred thoroughly to form a uniformly mixed organic polymer solid electrolyte solution;
[0106] II. Placing the acrylic-based oxide-type ceramic nanofibers obtained in step (2) on a polytetrafluoroethylene mold, and pouring a layer of the PVDF-LiTFSI organic polymer solid electrolyte solution obtained in step I on the surface thereof;
[0107] III. After the organic solvent acetonitrile is completely volatilized, the composite solid electrolyte membrane is separated from the mold and vacuum dried at 50°C for 24 hours to remove residual acetonitrile and adsorbed H2O, and the total thickness of the acrylic fiber-based LLZTO ceramic composite solid electrolyte is controlled at 90-110 μm.
[0108] The line sweep voltammetry (LSV) diagram of the Li / solid electrolyte / stainless steel battery with acrylic fiber-based LLZTO ceramic composite nanofiber solid electrolyte prepared in this embodiment is shown in Figure 7 ; The cycling performance diagram of Li / solid electrolyte / Li symmetric battery is shown in Figure 8 .
[0109] Example 5
[0110] A method for preparing an acrylic fiber-based ceramic composite nanofiber solid electrolyte, the specific steps of the method are as follows:
[0111] (1) Preparation of oxide-type ceramic nanoparticles:
[0112] 1mmol Li2CO3, 1mmol La2O3, and 4mmol TiO2 precursor salt were placed in a ball mill. Considering the volatilization of lithium and the Li 3x La (2 / 3)-x The decomposition of TiO3 (LLTO) requires the addition of 15% Li2CO3. The mixed ball milling was carried out for 12 hours with isopropanol as the ball milling medium, and the zirconia grinding ball was used at a ball milling speed of 300rpm. The ball-milled mixture was dried in an oven at 80°C for 12 hours. Then, it was calcined at 900°C for 12 hours, pressed under a pressure of 15MPa, sintered in an air atmosphere, and then ball milled for 12 hours to obtain oxide-type LLTO ceramic nanoparticles.
[0113] (2) Preparation of acrylic-based oxide-type ceramic nanofibers:
[0114] 1g of civilian acrylic yarn and 0.08g of conductive lithium salt were dissolved in 9g of N,N-dimethylformamide solvent, and stirred at room temperature to obtain an acrylic solution; 0.15g of ceramic nanoparticles and 0.25g of zinc acetate (Zn(Ac)2) were added to the acrylic solution, stirred and dispersed evenly at room temperature to obtain an acrylic-based ceramic composite solution, which was stirred at 80°C for 90min to obtain an electrospinning precursor solution; under the spinning conditions of an electrostatic voltage of 12kV, a spinning distance of 12cm, a spinning solution flow rate of 0.7mL / h, and a drum speed of 350rpm, the precursor solution was spun into a nanofiber membrane, and then vacuum dried at 60°C for 24h, taken out and placed in a glove box filled with argon for standby use, to obtain acrylic-based oxide-type LLTO ceramic nanofibers.
[0115] (3) Preparation of acrylic-based ceramic composite nanofiber solid electrolyte:
[0116] Ⅰ. 2.45 g PMMA and 0.8 g LiTFSI were vacuum dried at 50°C and 100°C for 24 h, respectively, and then dissolved in 50 mL acetonitrile and stirred thoroughly to form a uniformly mixed organic polymer solid electrolyte solution;
[0117] II. Placing the acrylic oxide-based ceramic nanofibers obtained in step (2) on a polytetrafluoroethylene mold, and pouring a layer of the PMMA-LiTFSI organic polymer solid electrolyte solution obtained in step I on the surface thereof;
[0118] III. After the organic solvent acetonitrile is completely volatilized, the composite solid electrolyte membrane is separated from the mold and vacuum dried at 50°C for 24 hours to remove residual acetonitrile and adsorbed H2O, and the total thickness of the acrylic fiber-based LLTO ceramic composite solid electrolyte is controlled at 90-110 μm.
[0119] The long-term cycle performance of the Li / solid electrolyte / LiFePO4 all-solid-state battery of the acrylic fiber-based LLTO ceramic composite nanofiber solid electrolyte prepared in this embodiment is shown in FIG. Fig. 9 .
[0120] in conclusion:
[0121] The scanning electron microscope (SEM) photograph of the LLZTO oxide ceramic nanoparticles prepared in Example 1 is as follows: Figure 2 As shown, the ceramic nanoparticles present a cubic phase structure, with uniform particle morphology, dense morphology and well-grown particles.
[0122] The SEM images of the acrylic oxide-type LLZTO ceramic nanofibers prepared in Example 1 are as follows: Figure 3As shown in the figure, the ceramic nanoparticles are evenly dispersed on the nanofibers and the fiber structure remains intact. This not only avoids the aggregation of ceramic fillers in the composite solid electrolyte, but also provides a good solution for Li + It provides a continuous and fast transmission path, which helps to improve the ionic conductivity of the electrolyte. In addition, there are many pores in the acrylic oxide-based LALZO ceramic nanofiber framework, which is conducive to the subsequent "polymer-conductive lithium salt" solution to fully penetrate into the porous ceramic network, forming a tight ceramic / polymer interface, thereby increasing the ion conduction rate at the interface and reducing the interface resistance between the two.
[0123] The surface SEM photo of the acrylic fiber-based LALZO ceramic composite nanofiber solid electrolyte prepared in Example 2 is as follows: Figure 4 As shown, the surface of the ceramic composite nanofiber solid electrolyte is flat and smooth with a few textures. This is due to the penetration of the organic polymer solution into the ceramic nanofibers during the pouring of the PEO-LiTFSI polymer solid electrolyte solution and the volatilization of acetonitrile in the solution after subsequent pouring.
[0124] The EIS and Arrhenius curves of the stainless steel / solid electrolyte / stainless steel symmetric cells of the acrylic fiber-based LALZO ceramic nanofiber composite solid electrolytes with different LALZO contents prepared in Example 3 are shown as follows: Figure 5 and Figure 6 As shown. The resistance of the stainless steel symmetrical battery of the composite solid electrolyte varies with the increase of the content of different ceramic nanoparticles. The addition of ceramic nanoparticles reduces the resistance of the composite solid electrolyte. The composite solid electrolyte with large resistance not only affects the overall ionic conductivity of the electrolyte, but also increases the resistance of the electrolyte / electrode interface in the all-solid-state lithium battery, which is extremely unfavorable to the overall electrochemical performance of the battery. Therefore, the preferred ceramic nanoparticle content is 15%. It is calculated that the ionic conductivity of the acrylic-based ceramic composite nanofiber solid electrolyte with 15% ceramic nanoparticles at 30°C is as high as 9.34×10 -5 S cm -1 The high ionic conductivity is mainly due to two reasons: first, the ceramic nanofiber network forms a long-distance continuous 3D ion-conducting transmission path, which accelerates the Li + transmission; secondly, the oxide ceramic filler reduces the crystallinity of the polymer and accelerates the movement of the polymer chain segments, making Li + Easier to migrate in polymer matrix.
[0125] The line sweep voltammetry (LSV) diagram of the Li / solid electrolyte / stainless steel battery with acrylic fiber-based LLZTO ceramic composite nanofiber solid electrolyte prepared in Example 4 is shown in FIG. Figure 7As shown, it can be seen that the Li / solid electrolyte / stainless steel battery has a wide electrochemical window at 50°C.
[0126] The cycle performance of the Li / solid electrolyte / Li symmetric battery of the acrylic fiber-based LLZTO ceramic composite nanofiber solid electrolyte prepared in Example 4 is shown in FIG. Figure 8 The voltage fluctuation of the symmetrical lithium battery is very small, with almost no obvious change, always maintained at around 0.08V, and can be stably cycled for more than 820h. This shows that Li + It can be orderly transferred inside the ceramic composite nanofiber solid electrolyte and uniformly deposited at the interface, thus forming a stable solid electrolyte / lithium metal interface layer.
[0127] The long-term cycle performance of the Li / solid electrolyte / LiFePO4 all-solid-state battery of the acrylic fiber-based LLTO ceramic composite nanofiber solid electrolyte prepared in Example 5 is as follows: Fig. 9 After 100 cycles, the all-solid-state battery still has 135.8 mAh g -1 The battery has a high discharge capacity, an average coulombic efficiency of more than 99%, and excellent cycle stability.
[0128] The above-mentioned embodiments prepare different types of acrylic-based oxide-type ceramic nanofibers, including garnet-type and perovskite-type ceramic composite nanofibers. Therefore, the method of preparing acrylic-based ceramic composite nanofibers by electrospinning waste acrylic yarn and oxide-type ceramic fillers in the present invention is suitable for the preparation of acrylic-based nanofibers of various types of oxide ceramics.
[0129] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A method for preparing an acrylic-based ceramic composite nanofiber solid electrolyte, characterized in that The method comprises the following steps: S1. Preparation of electrospinning precursor solution: a. dissolving acrylic yarn and conductive lithium salt in a solvent N,N-dimethylformamide to obtain an acrylic solution; b. adding oxide-type ceramic nanoparticles and zinc acetate to the acrylic fiber solution, stirring and dispersing them uniformly at room temperature, and then stirring at a temperature of 70-90° C. to obtain an electrospinning precursor solution; The amount of oxide-type ceramic nanoparticles added is 5-20% of the weight of the acrylic yarn, and the amount of zinc acetate added is 15-30% of the weight of the acrylic yarn; S2. Preparation of acrylic-based oxide-type ceramic nanofibers: The electrospinning precursor solution obtained in S1 is electrospinned into a nanofiber membrane, and then vacuum dried at 60±10° C. to obtain acrylic-based oxide-type ceramic nanofibers; S3. Preparation of organic polymer solid electrolyte solution: The polymer that can be used as a solid electrolyte and the conductive lithium salt are vacuum dried in a temperature range below their respective melting points for later use; Then, the polymer and the conductive lithium salt are dissolved in the organic solvent acetonitrile and stirred sufficiently to form a uniformly mixed organic polymer solid electrolyte solution; the weight ratio of the polymer to the conductive lithium salt is 2 to 4:1; S4. Preparation of acrylic-based ceramic composite nanofiber solid electrolyte: Finally, the acrylic-based oxide-type ceramic nanofiber obtained in S2 is placed on a mold, and a layer of the organic polymer solid electrolyte solution obtained in S3 is poured on the surface of the mold; After the organic solvent acetonitrile is completely volatilized, the mold is removed and vacuum dried to obtain an acrylic-based ceramic composite nanofiber solid electrolyte.
2. The preparation method according to claim 1, characterized in that: The acrylic yarn is textile waste material or leftover acrylic yarn for civil use and clothing.
3. The preparation method according to claim 1, characterized in that: The weight ratio of the acrylic yarn to the conductive lithium salt in step S1 a is 1:0.8-1.
4. The preparation method according to claim 1, characterized in that: The preparation method of the oxide-type ceramic nanoparticles described in S1 is as follows: placing a metal ion precursor salt containing an oxide-type ceramic solid electrolyte in a ball mill, adding an excess of Li2CO3 precursor salt as a compensator, mixing the precursor salt powder in propylene glycol, ball milling, calcining, and ball milling again to obtain oxide-type ceramic nanoparticles; The metal ion precursor salt is selected from garnet type, NASICON type, perovskite type or antiperovskite type ceramic precursor salt.
5. The preparation method according to claim 1, characterized in that: In step b of S1, the amount of zinc acetate added is 20-25% of the weight of the acrylic yarn.
6. The preparation method according to claim 1, characterized in that: In S2, The spinning parameters are static voltage 10-15 kV, spinning distance 10-15 cm, spinning solution flow rate 0.5-1.0 mL / h, and spinning drum speed 300-400 rpm.
7. The preparation method according to claim 1, characterized in that: In S1, the conductive lithium salt is selected from one or more of lithium halide (LiX, X = F, Cl, Br, I), lithium bis (trifluoromethylsulfonyl) imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4); In S3, the polymer is selected from a mixture of one or more polymers selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinyl chloride (PVC); the conductive lithium salt is selected from one or more of lithium halides (LiX, X=F, Cl, Br, I), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4).
8. The preparation method according to claim 1, characterized in that: The polymer and the conductive lithium salt in S3 are stirred in acetonitrile for 24-48 hours.
9. The preparation method according to claim 1, characterized in that: The vacuum drying temperature of the acrylic-based ceramic composite nanofiber solid electrolyte in S4 is 50°C±5°C, and the drying time is 24h±5h.
10. An acrylic fiber-based ceramic composite nanofiber solid electrolyte for a flexible solid-state lithium battery, the composite material being prepared by the preparation method according to claim 1.